A qualitative study of naturopathy in rural practice: A focus upon naturopaths' experiences and perceptions of rural patients and demands for their services - Wardle Jon L; Adams Jon; Lui Chi-Wai (BMC, 2010)
Abstract Background Complementary and alternative medicine (CAM) use - of which naturopathy constitutes a significant proportion - accounts for approximately half of all health consultations and half of out-of-pocket expenditure in Australia. Data also suggest CAM use is highest amongst rural Australians. Unfortunately little is known about the grass-roots reality of naturopathy or other CAM use in rural regions. Methods Semi-structured interviews were conducted with 20 naturopaths practising in the Darling Downs region of South-East Queensland to assess their perceptions and experiences of rural patients and demand for their services. Results Naturopaths described strong demand in rural areas for their services and perceived much of this demand as attributable to cultural traits in rural communities that served as pull factors for their naturopathic services. Such perceived traits included a cultural affinity for holistic approaches to health and disease and the preventive philosophy of naturopathy and an appreciation of the core tenet of naturopathic practice to develop closer therapeutic relationships. However, cost and a rural culture of self-reliance were seen as major barriers to naturopathic practice in rural areas. Conclusions Demand for naturopathic services in rural areas may have strong underlying cultural and social drivers. Given the apparent affinity for and increasingly large role played by CAM services, including naturopathic medicine, in rural areas it is imperative that naturopathic medicine and the CAM sector more broadly become a core focus of rural health research.